On the influence of multidirectional irregular waves on the PeWEC device - Cervelli, Giulia; Battisti, Beatrice; Mattiazzo, Giuliana (Frontiers in Energy Research, 2022)
Wave energy is a promising renewable resource for its reliability and power density, and many technological milestones have been achieved. Significant efforts are made to design and optimize Wave Energy Converters (WECs); however, analyses are often limited to simplified conditions. Among such restrictive assumptions, waves are frequently described utilizing monodirectional spectra, thus leading to approximate evaluations, also in terms of absorbed power. In real sea conditions, the waves are multidirectional, and the analysis as a 2D superposition of multiple wave components should be investigated. In particular, linear waves can be analyzed as a sum of sine waves characterized by different amplitudes, frequencies, phases and directions. The case study device analyzed in this paper is PeWEC (Pendulum Wave Energy Converter), a rotating mass device that converts energy based on pitch motion, moored through a spread catenary mooring system. The sea states investigated are those of the island of Cyprus. The spectrum is defined as the combination between the JONSWAP frequency spectrum and the cos-2s directional spectrum. To compute the sea elevation components the Deterministic Amplitude Scheme (DAS) method is used. The forcing acting on the device, the mooring loads and the device motions are examined and compared to quantify the error produced by the monodirectional approximations. The time domain solver OrcaFlex is employed to investigate the interaction of the waves with the moored hull. Compared with the multidirectional analysis, the monodirectional approximation generates an overestimation of the pitch by 5% and of the surge by 3%, highlighting the importance of taking spreading into account if the device is directional.